Inhibition of vascular endothelial growth factor‐A downregulates angiogenesis in psoriasis: A pilot study - Andrea Luengas‐Martinez; Dina Ismail; Ralf Paus; Helen S. Young (Wiley, 2023)
Abstract Background Vascular Endothelial Growth Factor (VEGF)‐A‐mediated angiogenesis participates in the pathogenesis of psoriasis, thus inviting the hypothesis that anti‐VEGF‐A therapy could be beneficial in psoriasis. While anti‐angiogenic agents are used in oncology and ophthalmology, these therapeutic strategies remain unexplored for the management of psoriasis. Objective Our objective was to investigate ex vivo how VEGF‐A blockade impacts blood vessels, epidermis and immune cells in organ‐cultured plaque and non‐lesional skin from patients with psoriasis. Methods Skin biopsies from patients with psoriasis (n = 6; plaque and non‐lesional skin) and healthy controls (n = 6) were incubated with anti‐VEGF‐A monoclonal antibody (bevacizumab, Avastin®) or a human IgG1 isotype control for 72‐h in serum‐free organ culture. CD31/LYVE‐1, Ki‐67, and mast cell tryptase expression were assessed by quantitative immunohistomorphometry. VEGF‐A levels in plasma, PBMCs and skin culture supernatants were measured. Results Inhibition of VEGF‐A blocked all free VEGF‐A ex vivo, reduced blood vessel area and the number of blood vessel endothelial cells in plaques of psoriasis (*p < 0.05). The treatment effect correlated significantly with levels of VEGF‐A in organ culture supernatants (r = 0.94; *p < 0.05) from plaque skin and with plasma levels of VEGF‐A from patients with psoriasis (r = 0.943; *p = 0.017). Conclusions These ex vivo data are the first studies to objectively investigate the potential of VEGF‐A inhibition as a novel adjuvant treatment strategy for psoriasis. Taken together, our data encourage further investigation by clinical trial to explore whether downregulating pathological angiogenesis has clinical utility, especially in patients with severe psoriasis or those with elevated levels of VEGF‐A in plasma and/or skin.